Determinants influencing the implementation of community health management for cognitive impairment: a qualitative study - Dongsheng Bian; Weiwei Zhang; Chenhao Yu; Xiao Han; Bu Zhao; Pairizati Abulikemu; Chenshu Shi; Yihui Wang; Guohong Li (BMC Geriatrics)
Abstract Background Cognitive impairment constitutes a significant global public health challenge, particularly for countries or regions experiencing the largest increases in aging populations. Most countries have reached a consensus that cognitive impairment screening, care, and intervention should be conducted within community settings. Objective To identify multilevel barriers and facilitators for community health management for cognitive impairment, this study utilized the Consolidated Framework for Implementation Research (CFIR) to systematically evaluate the implementation of strategies for managing cognitive impairment in Shanghai, China. Methods A semi-structured interview guide was developed based on the CFIR. Purposeful sampling was used to select 14 stakeholders from diverse sectors, including public health authorities, community health service centers, and experts in health management related to cognitive impairment, for semi-structured interviews. CFIR served as the coding framework for inductive analysis to identify and clarify the facilitators and barriers to cognitive impairment health management within the existing policy environment. Results Qualitative interviews with stakeholders in community-based cognitive impairment health management revealed eight facilitators and ten barriers. The facilitators included enhanced social engagement for older adults, efficient digital tools, a supportive policy environment, adequate funding, integration into basic public health services, sufficient community human resources, supportive internal and external teams, and health education. Collectively, these factors fostered a conducive environment for effective cognitive impairment health management. In contrast, the identified barriers comprised a lack of validation for smart tools, absence of collaborative mechanisms, insufficient incentives for primary care physicians (PCPs), a lack of long-term mechanisms, inadequate professional expertise, low energy levels, limited training channels, insufficient disease awareness among older adults, absence of standardized implementation plans, and superficial work practices. These barriers hindered the effective execution of community-based cognitive impairment health management strategies. Conclusion This study identified the primary facilitators and barriers to community-based cognitive impairment management within the context of current policies. To enhance the effectiveness of interventions, policymakers, health departments, and community organizations should actively address the identified barriers and leverage the facilitators. Additionally, the findings provide valuable insights for other countries facing similar challenges in cognitive impairment management. Future research should focus on integrating these factors into practical applications and evaluating the effectiveness of such interventions. Clinical trial number Not applicable.